2021
DOI: 10.4254/wjh.v13.i4.456
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patients (≥ 80 years) with acute calculous cholangitis have similar outcomes as non-elderly patients (< 80 years): Propensity score-matched analysis

Abstract: BACKGROUND Acute cholangitis (AC) is a disease spectrum with varying extent of severity. Age ≥ 75 years forms part of the criteria for moderate (Grade II) severity in both the Tokyo Guidelines (TG13 and TG18). Aging is associated with reduced physiological reserves, frailty, and sarcopenia. However, there is evidence that age itself is not the determinant of inferior outcomes in elective and emergency biliary diseases. There is a paucity of reports comparing clinical outcomes amongst elderly patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Singapore’s propensity score–matched analysis reported an overall in-hospital mortality rate of 4.6%, a 30-day mortality rate of 7.4%, and a 90-day mortality rate of 8.5%. 9 The mortality rate of SAC using the currently revised TG13/18 severity assessment was 5.1% in a joint study between Japan and Taiwan. There is no dispute that the mortality rate of SAC is high; 10 however, problems with the diagnostic criteria for SAC have also been highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Singapore’s propensity score–matched analysis reported an overall in-hospital mortality rate of 4.6%, a 30-day mortality rate of 7.4%, and a 90-day mortality rate of 8.5%. 9 The mortality rate of SAC using the currently revised TG13/18 severity assessment was 5.1% in a joint study between Japan and Taiwan. There is no dispute that the mortality rate of SAC is high; 10 however, problems with the diagnostic criteria for SAC have also been highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Inferior clinical outcomes in the elderly could be attributed to increased medical co-morbidity, malnutrition, frailty, diminished physiologic reserves, immunosenescence, altered pharmacokinetics and pharmacodynamics, polypharmacy, and institutionalization [ 20 - 22 ]. Though the World Health Organization has defined young elderly (aged 65-85 years) and old elderly (over 85 years), many authors continue to use the age cut-offs of 70 years, 75 years, and 80 years to study the impact of age [ 6 , 12 , 23 ]. The TG has made efforts to standardize diagnostic and severity stratification criteria, and the system is regularly reviewed and updated.…”
Section: Discussionmentioning
confidence: 99%
“…In a propensity-score matched study including 224 patients AC patients (112 patients ≥ 80 years, 112 patients < 80 years age), Chan et al . reported no statistically significant differences in overall in-hospital mortality, 30-day mortality, and 90-day mortality between the elderly and non-elderly in both the unmatched and matched cohorts [ 12 ]. Thus, it is likely that mortality risk is not solely determined by age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study by Law and Li ( 19 ) on 319 patients (age ≥ 65 years old [52.7%]) showed that age ≥ 65 years old is associated with a higher mortality rate. Furthermore, old age is associated with the confounding effect of co-morbidity, which may worsen outcomes ( 20 ). However, there is a paucity of literature on the real impact of age on outcomes in PLA.…”
Section: Introductionmentioning
confidence: 99%